How Much Supporting Electrolyte Is Required to Make a Cyclic Voltammetry Experiment Quantitatively "Diffusional"? A Theoretical and Experimental Investigation - Dickinson, E; Limon-Petersen, J; Rees, N; Compton, R (2009)
Theory is presented for cyclic voltammetry at a hemispherical electrode under conditions where the electric field is nonzero and migration is significant to mass transport. The nonlinear set of differential equations formed by combining the Nernst-Planck equation and the Poisson equation are solved numerically, subject to a zero-field approximation at the electrode surface. The effects on the observed voltammetry of the electrode size, scan rate, diffusion coefficient of electroactive and supporting species, and quantity of supporting electrolyte are noted. Comparison is drawn with experimental voltammetry for the aqueous system [Ru(NH3) 6]3+/2- at a Pt macroelectrode with varying levels of supporting electrolyte KCl. The approximations concerned are shown to be applicable where the ratio of supporting (background) electrolyte to bulk concentration of electroactive species (support ratio) exceeds 30, and general advice is given concerning the quantity of supporting electrolyte required for quantitatively diffusion-only behavior in macroelectrode cyclic voltammetry. In particular, support ratios are generally required to be greater than 100 and certainly substantially greater than 26, as has been suggested for the steady-state case. © 2009 American Chemical Society.